Sędziowska ocena dowodów na przykładzie wyroku Roty Rzymskiej c. Defilippi z 26 lutego 2009 r. (incapacitas assumendi, exclusio boni sacramenti, exclusio boni coniugum) Część I - Góralski, Wojciech (Ius Matrimoniale, 2014)
A shift c. Defilippi of the Roman Rota examined a case (in the second instance) regarding annulment of marriage due to three reasons: 1) inability of the respondent to take essential marital obligations; 2) exclusion of marriage indissolubility by the respondent; 3) exclusion of spouses’ best interest by the petitioner. After examining evidence, the tribunal issued a decree on 26 February 2009 deciding that the marriage shall not be annulled under mentioned annulment titles. A detailed analysis of an extensive sentence (both in iure and in facto reasons) indicates that the tribunal made detailed and comprehensive evaluation of collected evidence, and evidence regarding exclusion of bonum sacramenti by the respondent in particular, because as regards the other two reasons, the difficulty level of adjudication was not high.